Metal Biocorrosion of a Water Well: A Case Study - Calbo, Vicente; Furlong, Octavio Javier; Julián, Silvia Viviana (KnE Engineering, 2018)
Recently, in the city of La Rioja, the Microbiologically-Induced Corrosion (MIC) phenomenon has been confirmed. The last studied case corresponds to the water well of the La Rioja Regional Faculty of the National Technological University (UTN), where the water well facilities showed signs of this phenomenon. These microorganisms catalyze the iron (and magnesium) oxidation reactions, solubilizing or solubilizing and precipitating the metal. Confirming the existence of the MIC phenomenon is essential to mitigate or solve the problem. The laboratory work consisted in processing pipe and pump samples extracted after the well ceased to be used, at three initial temperatures and with different culture media, trying to cultivate, reproduce, and isolate and identify the different species. Thus, through culture methodology, the existence of a mixed flora featuring iron bacteria and sulfate-reducing bacteria was confirmed. Complementary Scanning Electron Microscopy (SEM) and Energy-dispersive X-ray Spectroscopy (EDS) spectroscopy scans allowed to visualize the bacteria, the damage to the analyzed material, and the morphology of the bioprecipitation. This little-known phenomenon causes significant economic losses and should therefore be taken into account in the execution as well as the maintenance of wells. Keywords: Metal Corrosion, Microbiologically Induced Corrosion, Water Well, Bacteria.